The Ukrainian economyʼs competitiveness in the realities of European challenges - MAZARAKI , Анатолій; MELNYK , Тетяна (Ius Modernum, 2025)
The research relevance is determined by the specifics of the current stage of Ukraineʼs European integration, which is due to a complex of multidirectional influences, challenges and threats that affect Ukraineʼs ability to compete effectively in European markets. Implementing the provisions of the Association Agreement with the EU and focusing on the goal of obtaining full membership in the European Union, Ukraine must first of all ensure its gradual integration into the common economic and social space of the united Europe, integrating its values, relationships, standards, norms and "agendas" of social and economic development adopted by the EU institutions. A comprehensive analysis of internal and external factors affecting the process of Ukraineʼs accession to the EU has been carried out, such as the turbulence of geopolitical processes, problematic trends in the EU, internal social and economic deformations and complications of the economic situation, the impact of Russian aggression on Ukraineʼs movement towards the European community, etc. Given the analysis of external and internal threats and opportunities for Ukraineʼs European integration, the hypothesis was put forward, tested and confirmed regarding Ukraineʼs ability, despite external aggression and internal challenges, to continue the path aimed at establishing democratic values and freedoms, improving the institutions of the rule of law, strengthening the national social and economic space, and promoting the development of civil society. The main challenges from the EU, Ukraineʼs compliance with the economic criteria for accession, the current rates of economic growth, and the state of foreign trade with the European Union were considered. Special attention was paid to the problems of external debt, the significant difference in scale between the Ukrainian and EU markets, the spread of shadow schemes in the economy, corruption, offshoring, and raiding practices. The potential capabilities of Ukraine regarding proposals for the EU were analyzed and the conditions under which the state can become an equal member of the European community were outlined.